Early intervention of atopic dermatitis as a preventive strategy for progression of food allergy - Sweeney, Alyssa; Sampath, Vanitha; Nadeau, Kari C. (Allergy, asthma, and clinical immunology, 2021)
Background Atopic diseases, such as atopic dermatitis (AD) and food allergy (FA), have increased in prevalence in industrialized countries during the past few decades and pose a significant health burden. They appear to have a common underlying mechanism and a natural disease progression. AD is generally the first atopic disease to manifest followed by other atopic diseases, such as FA, allergic rhinitis, or allergic asthma suggesting that they are likely different manifestations of the same disease. Body Evidence suggests that allergic sensitization occurs through an impaired skin barrier, while consumption of these foods at an early age may actually result in tolerance. This has been termed the Dual-Allergen-Exposure hypothesis. Loss of barrier integrity has been hypothesized to enable penetration of allergens, pollutants, and microbes and initiation of an inflammatory immune cascade of events leading to sensitization. The immune dysfunction is thought to further exacerbate the impaired skin barrier to form a vicious cycle. There is much interest in preventing or protecting the skin barrier from developing a proinflammatory atopic state, which may potentially lead to the development of AD and subsequently, FA. Conclusion Research on preventing or treating skin barrier dysfunction is ongoing. A number of studies have evaluated the efficacy of emollients in preventing AD and FA with mixed results. Studies have differed in the study design, population characteristics, emollients type, and frequency, duration, and area of application. Emollient type has varied widely from oils, creams, petrolatum-based lotions, and trilipid creams. Current research is directed towards the use of trilipid emollients that are similar to the skin’s natural lipid composition with a 3:1:1 ratio of ceramides, cholesterol and free fatty acids and a pH that is similar to that of skin to determine their effectiveness for skin barrier repair and prevention of AD and FA.